Professional Learning Community: Analysis and Impact on the Quality of Learning in Nusantara Capital Buffer School (IKN) - Dinanty, Najwa Shabrina; Setiawan, Muhammad Andri; Putro, Hendro Yulius Suryo (International Journal of Asian Education, 2024)
This study aims to analyze the impact of the Professional Learning Community (PLC) on the quality of learning in Nusantara Capital Buffer Schools (IKN). A mixed-method approach, combining qualitative and quantitative elements, was employed to understand the phenomenon comprehensively. The results indicate a significant improvement in learning outcomes, as evidenced by the increase in the average post-test score (70) compared to the pre-test score (48.75). The PLC program provided a platform for teachers to collaborate, share insights, and develop effective strategies to address learning challenges. Furthermore, implementing the PLC fostered a more supportive school environment, making students feel more comfortable and engaged. The findings underscore the importance of enhancing and expanding PLC initiatives to improve students' academic and non-academic achievements. Practically, these results suggest that the PLC model can be a valuable tool for teacher development and improved student outcomes. Academically, this study contributes to the growing literature on collaborative learning environments and their role in enhancing educational quality.